Safe Lighting Point as a new component of road safety elements - Mitał, Robert; Latała, Dawid; Wachta, Henryk; Ejsmont, Mariusz; Wojewoda, Izabela; Kamiński, Tomasz; Karkowski, Michał; Kamińska, Ewa (Archives of Civil Engineering, 2026)
The paper presents the results of research, which included measurements carried out on A dedicated test track of the Road and Bridge Research Institute is related to the improvement of safety of road traffic users, in particular pedestrians, cyclists, scooter users, etc. An in-depth analysis of urban monitoring records of accidents in urbanised areas made it possible to conclude that in the event of a collision between a motor vehicle and a column, the lighting set is fragmented, which has a real impact on the risk to the health and life of vulnerable road users. Research work has therefore been undertaken to develop lighting column designs that fulfil the task of significantly improving safety, particularly for pedestrians and cyclists, in the event of a collision between a motor vehicle and a lighting column. The work was directed at analysing the results of measurements of key parameters of a lighting set structure consisting of a column shaft with movable fittings and a bracket. Based on the research material collected, proprietary design solutions for lighting columns were developed, significantly improving pedestrian safety while meeting the passive safety requirements of vehicle users.